First record of Esox cisalpinus (Teleostea: Esocidae) in Sardinia with insight on its mitochondrial DNA genetic variability. Issue 4 (1st October 2016) - Casu, M.; Scarpa, F.; Cossu, P.; Lai, T.; Curini-Galletti, M.; Varcasia, A.; Sanna, D.
Abstract: Esox cisalpinus (Teleostea: Esocidae) (syn. Esox flaviae ) is an Italian freshwater autochthonous fish, whose originary range is limited to the Northern and Central Italy. However, this species has historically been introduced in several areas of Southern Italy, mainly for recreational purposes. In this paper we report the first record of E. cisalpinus on the Sardinia island (Western Mediterranean, Italy), where the species has been recently introduced at least in one lake. The species identification and the population dynamics analysis were performed using mitochondrial markers. The level of genetic variability, compared to those of other peninsular populations of E. cisalpinus, was surprisingly high, and several never-before-described haplotypes were found. A total of 10 mtDNA haplotypes were found. Demographic analysis is suggestive of a population expansion. We hypothesise that E. cisalpinus has been introduced in the Sardinian lake by the releasing of a conspicuous number of individuals. Given the conservational and recreational interest that E. cisalpinus arouses, it would be advisable that Sardinian government focuses in the near future also on management measures of its Sardinian population.